Optimizing Unilateral Deep Inferior Epigastric Perforator Flap Breast Reconstruction: A Quality Improvement Study. Issue 6 (29th November 2022) - Stern, Carrie S.; Plotsker, Ethan L.; Nelson, Jonas A.; Matros, Evan; Kalandranis, Eleni; Fatterusso, Dana; Mooney, Colette; Chen, Yigu; Velzen, Jeena; Mehrara, Babak J.
ABSTRACT: Deep inferior epigastric perforator (DIEP) flap surgery commonly involves multiday hospitalization, although data suggest 95% of complications after unilateral DIEP flap breast reconstruction occur within the first 24 hours. The aim of this study was to decrease hospitalization time and optimize care of patients undergoing unilateral DIEP flap breast reconstruction. Our study followed Six Sigma's DMAIC (define, measure, analyze, improve, control) framework. First, we delineated the stakeholders involved in the process and defined workgroups based on temporal relation to the operation. We measured performance according to project SMART (specific, measurable, achievable, relevant, time bound) goals and subsequently conducted an analysis of inefficiencies. We then created new interventions for quality improvement. Control will entail ongoing monitoring to ensure progress is sustained after study completion. Our interventions lasted 6 months and included 70 patients. By actively striving to advance patients through postoperative milestones during their inpatient stay and creating an outpatient nursing roadmap including aspects of inpatient care, we decreased the median length of stay from 67.8 to 44.8 hours ( p < .001). After receiving nursing instruction, 77% of patients agreed that they felt ready to be discharged. Our study suggests that the DMAIC framework can decrease hospitalization time after DIEP surgery and spare resources for additional patients.